Improving Vocational Teachers' Data Modeling Competence through MATLAB and Python Training: : A Case Study at SMK Negeri Penerbangan Aceh - Muslimsyah Muslimsyah; Yuwaldi Away; Safrizal Razali (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This training program aimed to enhance data modeling competencies among vocational teachers at SMK Negeri Penerbangan Aceh through intensive one-day MATLAB and Python training. Employing a pre-test/post-test design with 14 participants using 5-point Likert scale instruments, the results demonstrated significant improvements across all measured aspects. Key findings revealed the highest growth in work productivity (28.6% increase from 54.3% to 82.9%) and software mastery (25.7% increase from 42.9% to 68.6%). Cluster analysis identified three developmental patterns: (1) technical competencies (>20%), (2) tool integration (15-20%), and (3) conceptual understanding (<15%). The outcomes validate the effectiveness of hands-on, case-based training approaches while highlighting the need for advanced technical support programs. Practical implications suggest developing tiered training models for vocational teachers to address digital transformation challenges.